2009
DOI: 10.4085/1062-6050-44.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Acute Whole-Body Cooling for Exercise-Induced Hyperthermia: A Systematic Review

Abstract: Objective: To assess existing original research addressing the efficiency of whole-body cooling modalities in the treatment of exertional hyperthermia.Data Sources: During April 2007, we searched MEDLINE, EMBASE, Scopus, SportDiscus, CINAHL, and Cochrane Reviews databases as well as ProQuest for theses and dissertations to identify research studies evaluating whole-body cooling treatments without limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
181
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 21 publications
8
181
1
2
Order By: Relevance
“…3,12,13,16 We demonstrated that the CS treatment produced faster cooling rates than no treatment; however, the rate of cooling was slower than that produced by currently recommended techniques. 3 We analyzed temperature responses to the treatment protocols using both T re throughout treatment and overall cooling rates. The rates of cooling during each protocol allowed for a more robust analysis as they incorporated changes in T re , thereby reducing variability.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…3,12,13,16 We demonstrated that the CS treatment produced faster cooling rates than no treatment; however, the rate of cooling was slower than that produced by currently recommended techniques. 3 We analyzed temperature responses to the treatment protocols using both T re throughout treatment and overall cooling rates. The rates of cooling during each protocol allowed for a more robust analysis as they incorporated changes in T re , thereby reducing variability.…”
Section: Discussionmentioning
confidence: 76%
“…The most severe exertional heat illness is exertional heat stroke (EHS), characterized by a core temperature above 408C and concomitant central nervous system dysfunction. [1][2][3][4][5] Early recognition and treatment of EHS yields the best possible patient outcomes. 6 Decreasing core temperature below 408C as quickly as possible reduces the likelihood of organ damage and concomitantly increases the rate of survival.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although some debate exists concerning the safest and most effective method of cooling the athlete, most studies indicate that water bath immersion produces the fastest decrease in core temperature [31]. Controversy also exists concerning the most appropriate temperature of the water bath [32].…”
Section: Exertional Heatstrokementioning
confidence: 99%